Implementasi In House Training (IHT) Untuk Meningkatkan Kualitas Kompetensi Pedagogik Guru SMK Negeri 1 Percut Sei Tuan Dalam Menyusun Perangkat Pembelajaran Silabus Dan RPP - Kasni Kasni (Pusdikra Publishing, 2021)
This study aims to improve the quality of the Pedagogical Competence of Teachers of SMK Negeri 1 Percut Sei Tuan in Developing Syllabus and Lesson Learning Devices. The method used is the School Action Research (PTS) method. The results of the study are